Antiquity Including the "East" As "Western Identity" - Helena Trindade Lopes, Maria; Gurgel Pereira, Ronaldo G. (IntechOpen, 2023)
The usages of the past, and of antiquity, were felt throughout history, reflecting the fabric of apologetic and ideological narratives. Antiquity is studied to understand time to understand the way in which the past is received, integrated, and used. This work gathers seven essays featuring case studies on ancient cultural identity via interdisciplinary approaches. Interdisciplinarity, thanks to the intersection of history, archaeology, and linguistics, corresponds to the transversal, comprehensive, and complex look essential to understand the intrinsic value of antiquity in each time and in each present. Ancient history and archaeology demonstrate how diverse the ancient world truly was. Socio-cultural change and dynamics in contact situations between groups of distinct cultures produced constant innovations and adaptations. In this book, the reader will access debates on intercultural experiences from the perspective of Phoenician colonists in Spain; the formation of a particular Greek identity built by Greek colonists in Sicily; the dramatic social and cultural transformations in the southern Levant following the regional transition to the Bronze Age; the integration of pre-Islamic Somalia in a trade network connected to the Mediterranean, from the Bronze to Iron ages; the multicultural influences inspiring the Book of Genesis; the cultural identity of early Christians as the New Testament is developed under the influence of Near Eastern traditions; and the complex multi-cultural and multi-ethnic dialogue behind the process of formation of Koine Greek during Byzantine times.